If 4x-2 equals 2x-34 then x is equal to -16. 4x is equal to 2x-322x is equal to -32x is therefore -16
x2 + 4x - 32 = (x + 8)*(x - 4)
4x=22.4 what is the value of x
x2+4x-32 = (x-4)(x+8) when factored
x2 - 4x - 32 = (x - 8)(x + 4)
48-4x-13=4x+32+x First combine like terms So 48-13-4x=35-4x 4x+x+32=5x+32 Get the x by itself by subtracting the 32 from both sides 35-4x=5x+32 -32 -32 3-4x=5x +4x +4x 3=9x Divide both sides by 9 to get x by itself 3/9=x Simplify 1/3=x
To solve 4x+3-x=4x-32 we use the additive property of equaility and add -3 to both sidesSo 4x-x=4x-32-3Simplify this by now subtracting 4x from both sides.-x=-35 or x=35Check it.3-35=-32 so it works.
The value of x is 11/2
If: 4x-8 = 32 Then: x = 10
If you mean 2x = 32 then x = 16 and 9-(4*16) = -55
If x = 3, 4x = 12
It can be (for x = -2.5) but not for any other value of x.
4x+32=-4x+16x4x+32=12x-4x -4x32=8x/8 /84=x
If that's +4x, the answer is (x - 4)(x + 8) If that's -4x, the answer is (x + 4)(x - 8)
4x + 32 = 4(x + 8)
x = -32/3
If you mean -(x^2) - 4x + 32, then a simple way to do this is to factor out -1 first: -((x^2) + 4x - 32). Then you need simply to factorise the part inside the brackets
if that's +32, it factors to -(x - 4)(x + 8)
No. Substitute the value 8 for x, and you have 4x +6 = 4(8) +6 = 32 +6 = 38.
If you mean: x+4x--9 = x+1 then 4x = -8 and x = -2
The value of x is the unknown variable and the given expression can be simplified to: 4x-15
4x +32 can be factorised as 4(x + 8). Other than that there is not much you can do with the expression.